2012
DOI: 10.1002/srin.201100335
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Strain Rate on Hot Ductility of a V‐Microalloyed Steel Slab

Abstract: The hot ductility and malleability of a vanadium-microalloyed steel is investigated by means of tensile and compression tests at temperatures ranging from 700 to 8508C and strain rates of 3 Â 10 À4 to 0.3 s À1 . The deformation tests are performed after austenitization and cooling to test temperature. The so-called second ductility minimum is located around 7508C for all strain rates except for the highest one, where no ductility trough is observed. Ductility steadily increases with strain rate at a given temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…[8][9][10] Furthermore, the method XCT has been successfully used to characterize samples from continuous casting regarding ductility, damage initiation, and fracture mechanism. [11][12][13] In general though, the evaluation of XCT-data of Fe-based materials can be rather difficult if the conditions mentioned above are not completely fulfilled. Therefore, XCT-data concerning steel samples have to be usually inspected in a manual way by individually examining the XCT-slices.…”
Section: X-ray-computed Tomographymentioning
confidence: 97%
“…[8][9][10] Furthermore, the method XCT has been successfully used to characterize samples from continuous casting regarding ductility, damage initiation, and fracture mechanism. [11][12][13] In general though, the evaluation of XCT-data of Fe-based materials can be rather difficult if the conditions mentioned above are not completely fulfilled. Therefore, XCT-data concerning steel samples have to be usually inspected in a manual way by individually examining the XCT-slices.…”
Section: X-ray-computed Tomographymentioning
confidence: 97%
“…The reasons for the decrease of hot ductility have been studied by many scholars. [3][4][5][6][7][8][9][10][11][12][13][14][15][38][39][40][41][42] Zhang et al indicated that hot ductility trough resulted from the formation of pro-eutectoid ferrite films along prior austenite grain boundaries. [38,39] The distribution of the impurities [40] or precipitation [39,41] containing Ti, Nb, B, etc.…”
Section: A Factors Influencing the Hot Ductilitymentioning
confidence: 99%
“…[14] By decreasing the strain rate, strain-induced precipitation takes place, and the formation of nitrides and carbides is increased. [15] The numerical simulation of CC was constrained due to the lack of high-temperature mechanical property data of the novel steels. These data can be obtained using specific process parameters corresponding to the actual production-line parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of cracking is strongly associated with the ductility of steel in the temperature range of the straightening stage of continuous casting (ranging from 700 to 1000 C), [1][2][3] besides casting parameters, such as casting speed and secondary cooling pattern. Boron-containing steels are very susceptible to slab corner cracking because of poor hot ductility.…”
Section: Introductionmentioning
confidence: 99%